PIN7 Auxin Carrier Has a Preferential Role in Terminating Radial Root Expansion in Arabidopsis thaliana - Ruiz Rosquete, Michel (Int J Mol Sci, 2018)
Directional growth of lateral roots is critical for radial expansion and soil coverage. Despite its importance, almost nothing is known about its molecular determinants. Initially, young lateral roots (LRs) grow away from the parental root, maintaining the angle acquired shortly after emergence. A second downwards bending response to gravity terminates the so-called plateau phase and thereby limits radial root expansion. Here, we show that the exit from the plateau phase correlates with an increase in auxin signalling at the tip of the LRs. Moreover, the increase in auxin levels induces the termination of the plateau phase, which requires PIN-FORMED (PIN) auxin efflux carriers. Our data suggests that the developmental increase in auxin triggers the preferential derepression of PIN7 in gravity-sensing columella cells. The subsequent polarization of PIN7 heralds the bending towards gravity and, hence, the exit from the plateau phase. This developmental framework reveals the distinct roles of PIN auxin efflux carriers in controlling the radial growth of root systems.